DAYA HAMBAT EKSTRAK ETANOL KULIT MANGGIS (Garcinia mangostana Linn) TERHADAP ZONA RADIKAL Candida albicans IN VITRO - , NINDY REVITA LAURENTIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Candida albicans is one of normal flora in the oral cavity. When their number is increased, they change into pathogenic which is associated with the decreased immune and bad oral health condition. Cases of infection caused by Candida sp increased in the past two decades, and 70-80% were caused by Candida albicans. The side effects and resistance of antifungal drugs often occured. Mangosteen as one of medicinal herbs that provides many advantages, one of them as an antifungal. The aim of this study was to determine the inhibition potential of mangosteen pericarp ethanol extract (Garcinia mangostana Linn) against in vitro Candida albicansâs radical zone. This study was a true experimental laboratory with post-test only control group design. The research was conducted using Candida albicans in growth medium contained Saboraud chloramphenicol agar in 5 petri dish. Each petri dish with 5 wells treated with the mangosteen pericarp ethanol extract (Garcinia mangostana Linn) with concentrations of 0%, 10%, 20%, 40%, meanwhile 10% ketoconazole was conducted as a positive control. In vitro Candida albicansâs radical zone was measured using a vernier caliper with accuracy 0.01 mm. Data were analyzed using one-way ANOVA test with a significant level of (Î±=0,05). The results showed the mean difference in the five treatment groups with a significance value of 0.000 (p <0.05). The results showed that the mangosteen pericarp ethanol extract (Garcinia mangostana Linn) had inhibition potential against in vitro Candida albicansâs radical zone and the most powerful antifungal concentration was 40%.